Triggers for multiple sclerosis relapse in Saudi Arabia: An exploratory cross-sectional study - Foziah J. Alshamrani; Azra Zafar; Mona H. AlSheikh; Abdullah S. Alamri; Alaa K. Alshammari; Modhi S. Alajmi; Mohammad A. Zeeshan; Ibrahim A. Alghnimi; Ghadeer M. Fardan; Mohammed F. Almuaigel (Journal of Family and Community Medicine)
BACKGROUND: Multiple sclerosis (MS) is an autoimmune demyelinating inflammatory disease that affects the central nervous system. Relapse of MS involves the development of new MS-related neurological symptoms or the worsening of existing symptoms for at least 24 h, at least 30 days after the start of the last relapse. Stress, lack of sleep, high/low temperatures, infections, missed doses of MS medications, high-altitudes, antibiotic use, the use of oral contraceptives, and smoking are possible triggers for an MS relapse. To our knowledge, no studies have identified triggers for MS relapse in Saudi Arabia. MATERIALS AND METHODS: This cross-sectional study was conducted among Saudi MS patients aged 16 years or older who met the criteria of relapsing-remitting MS (RRMS) or secondary-progressive MS (SPMS). Patients were recruited through Arfa MS society. Data collected included demographic information, type of MS, age at diagnosis, family history of MS, and possible trigger factors. Medical information was abstracted from electronic files whereas information about trigger factors was patients obtained through interviewing the patients. Categorical variables were presented as frequency and percentage, whereas mean and standard deviation were calculated for continuous variables. Chi-square test was used to compare the data across categorical variables. RESULTS: A total of 305 MS patients were included in the study. Majority of the participants were females (61.6%) and were aged >30 years (63.9%); 89.5% had RRMS and 11.1% patients had a family history of MS. Anxiety and stress were the most frequently reported triggers by the participants (77.4%). Anxiety and stress, sleep deprivation, and pregnancy or breastfeeding were significantly common in respondents aged <30 years (P < 0.05). CONCLUSION: This study is the first step toward identifying the triggers for MS relapse in Saudi Arabia. It will support the expansion of research for the establishment of strategies to avoid these triggers.